Update on the management of attention-deficit/hyperactivity disorder in children and adults: patient considerations and the role of lisdexamfetamine - Cowles, Brian J (Dove Medical Press, 2009)
Attention-deficit/hyperactivity disorder (ADHD) is a behavioral disorder characterized by atypical levels of inattention, hyperactivity, and impulsivity that impair daily living activities. Although commonly associated with children and adolescents, current literature and practice now demonstrate the impairment the disorder may impose on adults as well. Central nervous system (CNS) stimulant medications are the first-line therapy for ADHD. CNS stimulants include methylphenidate and amphetamine derivatives. Longer-acting formulations used once daily are often preferred to avoid medication administration during school or work as well as to avoid side effects associated with rapid fluctuations in serum concentrations associated with multiple daily dosing. Lisdexamfetamine, a new, novel amphetamine product, has been shown to provide efficacy upwards of 12 hours in children and adults with a side effect profile similar to those of other longer-acting amphetamine products. Owing to its unique prodrug composition and the need for oral administration to activate the medication, lisdexamfetamine may offer advantages in clinical situations where stimulant abuse is a concern.